O-033 Ruptured symptomatic cerebral artery aneurysms versus un-ruptured asymptomatic aneurysms: is there a protective effect of long-term aspirin use against aneurysm rupture?. (22nd July 2018) - Ali, M; Zitterkopf, Z; Aly, A; Walter, R; Mironov, A; Stavas, J
Abstract : Background and aims: Approximately 2% of the general population have saccular intracranial aneurysms that remain asymptomatic unless rupture occurs leading to subarachnoid hemorrhage. Spontaneous Subarachnoid Hemorrhage (SSAH) related rupture affects 9 per 1 00 000 persons per-year and associated with an approximately 40% case-fatality rate. Factors that contribute to intracranial aneurysm rupture are poorly understood. The hypothesis that aneurysmal wall inflammation contributes to the pathophysiology and likelihood of aneurysm rupture has been recently proposed. Aspirin is a potent cyclooxygenase-2 inhibitor and plays a role in the expression of multiple immune modulators that influence cerebral aneurysm formation and rupture. Currently there is no pharmacologic therapy for prevention of aneurysm progression and rupture. A retrospective analysis of the Healthcare Cost and Utilization Project National Inpatient Sample database (HCUP-NIS) from 2009 to 2014, was assessed for the association between long term aspirin use and risk of cerebral aneurysm rupture and the relationship between aspirin use and inpatient mortality after SSAH. Methods: Hospitalizations between 2009 and 2014 that included Un-ruptured Cerebral Artery aneurysm (UCA) (ICD-9-CM: 437.3) and SSAH (ICD-9-CM: 430 excluding 852.xx) were identified. Despite the lack of specific ICD code for non-aneurysmal SSAH (published estimates are 10%–20% of SSAH cases), the use of this method was validated in multiple studies to identify aneurysmal SSAH with high sensitivity and specificity. UCA and SSAH were compared in case-control design regarding odds of long term aspirin use. Similar analysis compared in-patients who survived or died after SSAH. The analysis accounted for the HCUP-NIS sampling design and hospital trend weights. Cross-sectional rates were compared using the modified Rao-Scott Chi Square test with multivariable logistic regression statistical analysis to calculate adjusted odds ratio, using SAS Version 9.4. The data base excluded aneurysm anatomic features and diagnostic imaging modality. Results: Hospitalizations for 224, 447 UCA and 143, 874 SSAH from 2009–2014, were included in the study, accounting for 15 and 10 hospitalizations per 100, 000 US population, respectively. The odds of using long term aspirin was lower in the SSAH group when compared to the UCA group (OR=0.46, 95% CI: 0.42–0.50, p<0.001) suggesting a protective effect of aspirin against aneurysm rupture. The SSAH patients who died in the hospital demonstrated lower odds of long term aspirin use (OR=0.74, 95% CI: 0.63–0.86, p=0.002). Conclusions: In this retrospective analysis, long term aspirin use was associated with statistically significant decreased odds of cerebral aneurysm rupture and less post rupture mortality. These findings may be due to protective anti-inflammatory mechanisms of aspirin although other unknown properties of ASA may provide pharmacologic regulation of cerebral aneurysm development and warrants further investigation. Disclosures: M. Ali: None. Z. Zitterkopf: None. A. Aly: None. R. Walter: None. A. Mironov: None. J. Stavas: 2; C; inRegen Biotechnology, Excelerate Health Ventures.